Serum neurofilament light concentration does not increase following exposure to low velocity football heading - Austin, K.; Lee, B. J.; Flood, T. R.; Toombs, J.; Borisova, M.; Lauder, M.; Heslegrave, A.; Zetterberg, H.; Smith, N. A. (Science and Medicine in Football, 2021)
Objectives: To investigate if heading frequency and impact biomechanics in a single session influence the concentration of serum neurofilament light (NF-L), a sensitive biomarker for axonal damage, up to 7 days after heading incident at ball velocities reflecting basic training drills. Methods: Forty-four males were randomized into either control (n = 8), 10 header (n = 12), 20 header (n = 12) or 40 header (n = 12) groups. Linear and angular head accelerations were quantified during heading. Venous blood samples were taken at baseline, 6 h, 24 h and 7 days after heading. Serum NF-L was quantified using Quanterix NF-L assay kit on the Simoa HD-1 Platform. Results: Serum NF-L did not alter over time (p = 0.44) and was not influenced by number of headers [p = 0.47; mean (95% CI) concentrations at baseline 6.00 pg · ml-1 (5.00-7.00 pg · ml-1); 6 h post 6.50 pg · ml-1 (5.70-7.29 pg · ml-1); 24 h post 6.07 pg · ml-1 (5.14-7.01 pg · ml-1); and 7 days post 6.46 pg · ml-1 (5.45-7.46 pg · ml-1)]. There was no relationship between percentage change in NF-L and summed session linear and angular head accelerations. Conclusion: In adult men, heading frequency or impact biomechanics did not affect NF-L response during a single session of headers at ball velocities reflective of basic training tasks.